A University-Led Contact Tracing Program Response to a COVID-19 Outbreak Among Students in Georgia, February–March 2021. (November 2022) - Harrington, Kristin R.V.; Siira, Meron R.; Rothschild, Elizabeth P.; Rabinovitz, Sharon R.; Shartar, Samuel; Clark, David; Isakov, Alexander; Chamberlain, Allison; Gelaye, Enku; Cegielski, J. Peter; Gandhi, Neel R.
Few reports have described how university programs have controlled COVID-19 outbreaks. Emory University established a case investigation and contact tracing program in June 2020 to identify and mitigate transmission of SARS-CoV-2 in the Emory community. In February 2021, this program identified a surge in COVID-19 cases. In this case study, we present details of outbreak investigation, construction of transmission networks to assess clustering and identify groups for targeted testing, and program quality metrics demonstrating the efficiency of case investigation and contact tracing, which helped bring the surge under control. During February 10–March 5, 2021, Emory University identified 265 COVID-19 cases confirmed by nucleic acid testing in saliva or nasopharyngeal samples. Most students with COVID-19 were undergraduates (95%) and were affiliated with Greek life organizations (70%); 41% lived on campus. Network analysis identified 1 epidemiologically linked cluster of 198 people. Nearly all students diagnosed with COVID-19 (96%) were interviewed the same day as their positive test result. Of 340 close contacts, 90% were traced and 89% were tested. The median time from contact interview to first test was 2 days (interquartile range, 0-6 days); 43% received a positive test result during their quarantine. The surge was considered under control within 17 days, after which new cases were no longer epidemiologically linked. Early detection through systematic testing protocols and rapid and near-complete contact tracing, paired with isolation and quarantine measures, helped to contain the surge. Our approach emphasizes the importance of early preparation of adequate outbreak response infrastructure and staff to implement interventions appropriately and consistently during a pandemic.